2022
DOI: 10.3389/fsurg.2022.992490
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of endometriosis with dienogest in combination with traditional Chinese medicine: A systematic review and meta-analysis

Abstract: BackgroundEndometriosis is now considered to be a systemic disease rather than a disease that primarily affects the pelvis. Dienogest (DNG) has unique advantages in the treatment of endometriosis, but it also has side effects. Alternatively, Traditional Chinese Medicine (TCM) has been used for over 2000 years in the treatment and prevention of disease and growing numbers of Chinese scholars are experimenting with the combined use of Dienogest and TCM for endometriosis treatment.ObjectivesThis review evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…At present, many studies have shown that TCM has a synergistic effect on the treatment of endometriosis. 26,27 The mechanisms involved include regulating the immune response, apoptosis, and angiogenesis, 28 which are consistent with our findings. However, many studies use Chinese herbal medicine directly, and the quality control may be unstable.…”
Section: Discussionsupporting
confidence: 90%
“…At present, many studies have shown that TCM has a synergistic effect on the treatment of endometriosis. 26,27 The mechanisms involved include regulating the immune response, apoptosis, and angiogenesis, 28 which are consistent with our findings. However, many studies use Chinese herbal medicine directly, and the quality control may be unstable.…”
Section: Discussionsupporting
confidence: 90%
“…These practices involve the utilization of many substances, including plants, animals, minerals, and their processed derivatives. Additionally, contemporary medicines developed using modern techniques, guided by Chinese medical principles, are also considered part of Chinese medicine (Wu et al, 2022). Traditional Chinese medicine (TCM) or TCM formulations have been employed for over 2000 years in the treatment and prevention of many ailments (Xie et al, 2013).…”
Section: Laboratory Examinationmentioning
confidence: 99%
“…Non-hormonal treatments for EM often involve the application of nonsteroidal antiinflammatory drugs (NSAIDs), certain antidepressants and anticonvulsant medications that can be used as first-line treatments to alleviate the symptoms of P2 TCM has a long history of use in treating various gynecologic diseases, and new research on TCM for the treatment of EM is reported annually (Figure 2) (34). One study showed that combining dienogest, a conventional western medical treatment for EM, with TCM resulted in better outcomes in patients who did not respond well to standard western medical treatments (9). Moreover, RCTs and meta-analyses have revealed that TCM management of female infertility can lead to improved pregnancy rates compared to western medical drug therapy (35).…”
Section: Western Medical Treatment In Endometriosismentioning
confidence: 99%
“…Gynecology in relation to traditional Chinese medicine (TCM) has a 3,000-year history (8). EM is recorded as Zhengjia in TCM books, and first mentioned in Huangdi Neijing (9). TCM is widely used as Chinese medicinal compounds, patented Chinese patent medicines and acupuncture (10); and is a popular treatment for EM in China due to its significant therapeutic function and few side effects.…”
Section: Introductionmentioning
confidence: 99%